Buyer preferences and supplier responsiveness on passion fruit in North Cotabato - Ebarle, Exegesis Jedidiah N.
This paper was conducted in order to determine the level of responsiveness of farmers (supplies) towards the preferences of fresh passion fruit consolidators (buyers) in some of the areas in North Cotabato, primarily in terms of the fruit's physical characteristics, such as skin color, fresh color, seed color, size, shape, surface appearance, maturity and cleanliness; and production process, whether organic or inorganic farming. A study on the market channel choice of farmers was also conducted so as to determine the factors affecting the farmers' market channel choice. Descriptive statistics and cross tabulation analysis were employed in determining the gaps between buyer preferences and supplier responsiveness. Results showed that there is a 77.8% responsiveness of farmers towards the consolidators' preferences. The main buying stations in North Cotabato were located in Makilala, Kidapawan and Antipas. The market channel choice study, on the other hand, was analyzed using the binary logit regression and was further supplemented by another model using multiple linear regression. The first generated model using binary logit showed to be unacceptable and incurred insignificant variables. The second model using multiple linear regression, however, showed that farm size was the only variable that significantly affects the farmers' market channel choice. Direct marketing had a negative relationship with profitability because of higher transportation and transaction costs. Neverthelesss, the implications and analysis on the first generated model as to why it resulted to insignificant variables remain acceptable and justifiable.
Thesis, Undergraduate (BS Agribusiness Economics) -- U. P. Mindanao